2009
DOI: 10.1021/cm901222j
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Conversion of Carbon-Encapsulated Metal Nanoparticles to Hollow Nanoparticles

Abstract: We synthesized R-Fe 2 O 3 hollow nanoparticles by directly oxidizing the carbon-encapsulated iron carbide (Fe 3 C@C) nanoparticles in air. In this paper, the conversion mechanism of Fe 3 C@C to hollow nanoparticles was deduced in detail by comparatively investigating the morphologies and compositions of the oxidized products at different oxidation stages using transmission electron microscope (TEM), high resolution TEM (HRTEM), energy-dispersive X-ray (EDX), X-ray diffraction (XRD), and X-ray photoelectron spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…97 The binding energy of Fe 2p 3/2 electron in Fe doped β-Mo 2 C is comparable to that in Fe 3 C (~707.50 eV) and Fe 5 C 2 (~707.00 eV). [98][99][100] Unexpected and important information has been collected from valence bands (VB) studies on Fe doped β-Mo 2 C materials as seen in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…97 The binding energy of Fe 2p 3/2 electron in Fe doped β-Mo 2 C is comparable to that in Fe 3 C (~707.50 eV) and Fe 5 C 2 (~707.00 eV). [98][99][100] Unexpected and important information has been collected from valence bands (VB) studies on Fe doped β-Mo 2 C materials as seen in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…Because the iron carbide sphere surfaces were covered with amorphous carbon, we employed 3-kV Ar ion bombardment to remove the surface layer to a depth of 50 nm. For the Fe 2p region, the two peaks at 707.45 and 720.28 eV suggested the presence of iron carbide components2021. The C1s spectrum was fitted with three components.…”
Section: Resultsmentioning
confidence: 99%
“…The outward diffusion of Fe may be the main type of diffusion during the removal of iron particles and this was also observed by other researchers. [32] To promote the outward diffusion of iron nanoparticles, there must be a driving force; one suggestion was particle melting. [33] It has been reported that iron nanoparticles become unstable when heated even at 250 8C.…”
mentioning
confidence: 99%